Water pollutant monitoring by a whole cell array through lens-free detection on CCD1. Issue 6 (21st March 2015) - Tsai, Hsieh-Fu; Tsai, Yi-Ching; Yagur-Kroll, Sharon; Palevsky, Noa; Belkin, Shimshon; Cheng, Ji-Yen
<x xml:space="preserve">Abstract</x> This is a portable system for water contamination monitoring. Using live bacterial cells as bioreporters, we integrate temperature control, microfluidic sample introduction, bioluminescence detection, and recording software into a complete system.